Development of a CRISPR/Cpf1 system for targeted gene disruption in Aspergillus aculeatus TBRC 277 - Abdulrachman, Dede; Eurwilaichitr, Lily; Champreda, Verawat; Chantasingh, Duriya; Pootanakit, Kusol (BMC biotechnology, 2021)
CRISPR-Cas genome editing technologies have revolutionized biotechnological research particularly in functional genomics and synthetic biology. As an alternative to the most studied and well-developed CRISPR/Cas9, a new class 2 (type V) CRISPR-Cas system called Cpf1 has emerged as another versatile platform for precision genome modification in a wide range of organisms including filamentous fungi. In this study, we developed AMA1-based single CRISPR/Cpf1 expression vector that targets pyrG gene in Aspergillus aculeatus TBRC 277, a wild type filamentous fungus and potential enzyme-producing cell factory. The results showed that the Cpf1 codon optimized from Francisella tularensis subsp. novicida U112, FnCpf1, works efficiently to facilitate RNA-guided site-specific DNA cleavage. Specifically, we set up three different guide crRNAs targeting pyrG gene and demonstrated that FnCpf1 was able to induce site-specific double-strand breaks (DSBs) followed by an endogenous non-homologous end-joining (NHEJ) DNA repair pathway which caused insertions or deletions (indels) at these site-specific loci. The use of FnCpf1 as an alternative class II (type V) nuclease was reported for the first time in A. aculeatus TBRC 277 species. The CRISPR/Cpf1 system developed in this study highlights the feasibility of CRISPR/Cpf1 technology and could be envisioned to further increase the utility of the CRISPR/Cpf1 in facilitating strain improvements as well as functional genomics of filamentous fungi.